METODE ISTINBATH DAN HUKUM ASURANSI SYARIAH MENURUT ORGANISASI KEAGAMAAN ISLAM DI INDONESIA - Ariyanto; Solihin, Dadin; Saefuddin, Aep; Hidayatul Ummah, Nida (Jurnal Pelita Nusa, 2025)
Sharia insurance is a contemporary issue that does not have an explicit basis in the Qur'an, Hadith, or the books of mu'tabarah from the four schools. Therefore, Islamic religious organizations in Indonesia, such as MUI, NU, Muhammadiyah, and PERSIS play an important role in establishing laws related to sharia insurance so that they become guidelines for the people. This study aims to explain the istinbath method used by the organization in determining the halalness of Sharia insurance. The research method used was a literature study and interviews with figures from each organization. The results of the study show that MUI uses the nash qoth'i, qauli, and manhaji approaches; NU uses qauli, ilhaqi, and manhaji; Muhammadiyah uses bayani, burhani, and irfani; while PERSIS uses istidlal on the Qur'an, Hadith, and ijtihad. Despite the differences in methods, all of these organizations concluded that sharia insurance is halal because it contains the value of helping (ta'awuni), bearing each other (takafuli), and bringing the common good (maslahah al-'ammah), which is in line with Maqāsid al-sharia, namely the maintenance of religion, soul, intellect, descendants, and property.